Level of Patient Satisfaction in the Dental Polyclinic of Puskesmas Merdeka Palembang - Nur Adiba Hanum; Dhandi Wijaya; Lilik Indrawati (Jurusan Keperawatan Gigi, Poltekkes Kemenkes Semarang, 2019)
Rapid economic growth makes competition and competition in the business world even tighter, as well as businesses in health services, which are required to be able to meet the needs and desires of patients who are not only limited to their services. Puskesmas that want to develop must be able to maintain patient loyalty by providing satisfaction to their patients by providing quality services. This study aims to determine the level of patient satisfaction on services at the Dental Polyclinic of the Puskesmas Merdeka. This research is a qualitative research conducted in March 2019 on 62 patients in the dental polyclinic during the period of March 2019 which was taken by accidental sampling. Data obtained using a questionnaire consisting of three variables, the professionalism of dental health workers, service systems, and facilities in the dental polyclinic. The level of patient satisfaction is the percentage of the total score against the total score and categorized as very satisfied, satisfied, quite satisfied, dissatisfied, and very dissatisfied. The results showed that the level of patient satisfaction on the professionalism of dental health workers, service systems, and facilities in the dental polyclinic was 87.01%, 84.71%, and 84.55%, and all in very satisfied category. It can be concluded that the services at the Dental Polyclinic of the Puskesmas Merdeka is a quality service.